The synergy between percutaneous coronary intervention with TAXUS and cardiac surgery study: A surgical perspective - van Wyk, Jacques (SA Heart Journal, 2017)
he SYNTAX (The Synergy between percutaneous coronary intervention with TAXUS and cardiac surgery) study is an important study to indicate the best treatment option for patients who have three vessel coronary artery disease and/or left main stem coronary disease (LMD). CABG (coronary artery bypass grafting) is still the preferred therapy for these patient groups with proven low mortality and excellent long term survival rates. PCI-DES (percutaneous coronary intervention with drug eluting stents) is a relative non-invasive procedure with comparable short and medium term survival, but with a much higher repeat revascularisation rate. The SYNTAX Study enrolled 1800 patients in a randomised arm and 1275 in a registry arm. A SYNTAX Score was developed to assess the lesion morphology. At 12 months follow-up in the randomised group there was an increased death rate (4.3% vs 3.5%), myocardial infarction rate (4.8% vs 3.2%) and repeat revascularisation rate (13.7% vs 5.9%) in the PCI-TAXUS (percutaneous coronary intervention with TAXUS stent) group compared to the CABG group. This trend continues up to 24 months with increased death rate (6.2% vs 4.9%), myocardial infarction rate (5.9% vs 3.3%), repeat procedure rate (17.4% vs 8.6%) and MACCE rate (23.4% vs 16.3%) in the PCI group compared to the CABG group. The aim of the SYNTAX Study was to prove non-inferiority of PCI (percutaneous coronary intervention) compared to CABG in these patient populations. Non-inferiority of PCITAXUS compared to CABG in this study population could not be shown at 12 or 24 months. The cerebrovascular event rate was higher in the CABG group in both study arms (2.2% vs 0.6%) in the first year, but a nearly similar CVA rate during the next 12 months. The study will terminate in 2011 and will give much-needed information regarding the optimal treatment option in patients with three vessel disease and/or left main disease.